THE INTEGRATION OF PARAM AS TRADITIONAL MEDICINE OF KARO ETHNIC IN SCIENCE LEARNING AT JUNIOR HIGH SCHOOL BY USING ETHNOSCIENCE APPROACH - Puspita, Wina Dyah; Suriani, Cicik; Nasution, Aswarina; Sanimah (Universitas Negeri Medan, 2025)
This study aims to examine the indigenous knowledge of the traditional oil formulation of the Karo ethnic using an ethnoscience approach. The ethnoscience approach is a learning method that reconstructs indigenous science into scientific knowledge. This research is a descriptive qualitative study. Data was collected through a literature review, observations, and interviews with the Karo ethnic residing in Medan. The results show that the Paeam formulation involves various types of spices, leaves, and roots. There are 4 plant species used as ingredients in the preparation of param, they belong to 8 different plant families.The family with the most species is Zingiberaceae, with 6 species. Based on the results obtained, the study further explores indigenous science using an ethnoscience approach. The reconstruction of indigenous knowledge into scientific knowledge in the processing of Paraml can be observed in the following stages: 1) The collection of spices and, 2) The Process of Making Param. The integration of param processing into Junior High School science learning can be seen in the topics of classification of living things (grade VII), element, compound, and mixture (grade VIII), and temperature, heat, and expansion (grade VII). It can be concluded that the processing of param is integrated with science learning at the junior high school.